Rotational Barrier and Conjugation: Theoretical Study of Resonance Stabilization of Various Substituents for the Donors NH2 and OCH3 in Substituted 1,3-Butadienes - Ali Hussain Yateem (Indonesian Journal of Chemistry, 2019)
The barrier to internal rotation around the central C2–C3 single bond of a series of (1E)-monosubstituted 1,3-butadienes and (1E,3E)-1-Y-4-X-disubstituted butadienes, with Y=NH2 or OCH3 and X=NO2, CHO, COOH, CN, CF3, Cl or F, were studied at the density functional w B97X-D/6-31G∗∗ level. The effect of substituents on π-conjugation in disubstituted 1,3-butadienes was studied by correlating the calculated internal rotational barriers with the difference in structural, atomic and molecular properties between the transition state TS and the s-trans conformers. The calculated differences in lengths of C–C, C–NH2 and C–OCH3 single bonds, N-H-N, and C-O-CH3 angles, NH2 out-of-plane angle, natural charges on amino nitrogen and methoxy oxygen, and the maximum electrostatic potential on amino hydrogens, were found to correlate strongly with the rotational barriers. The conjugative interaction was strongly stabilized in the case of strong π-electron acceptors such as NO2 or CHO and is slightly or negligibly affected with Cl and F groups. The resonance stabilization with the remaining acceptors decreases in the order COOH > CN > CF3. Acceptors X maintain their relative order of stabilization for the two donors, and NH2 is more stabilizing. Dominant resonance structures are suggested for highly and negligibly conjugated systems.